Interpretation, jurisdiction, and the authority of law - Endicott, T (American Philosophical Association (APA), 2007)
People can be autonomous, if they are subject to authority. In particular, they can be autonomous if they are subject to the authority of law. I defend the first claim through a study of Joseph Raz's compelling account of authority; I claim that his work leads to the conclusion that autonomous judgment is needed to determine the jurisdiction of an authority, and to interpret its directives. I defend the second claim by arguing (contrary to remarks by Raz) that law does not claim unlimited jurisdiction, and need not claim unlimited scope for its directives. But the requirements of the rule of law create a standing risk that the law will not adequately recognize the autonomy of its subjects, because of its artificial techniques for controlling its own jurisdiction and for controlling the scope of its own directives.